Non-Uniform Attenuation Correction for Myocardial SPET Using Two Gd-153 Line Sources - Kluge, R.; Seese, A.; Sattler, B.; Knapp, W. H. (Nuklearmedizin - NuclearMedicine, 1996)
Aim: This study deals with the effect of the non-uniform attenuation correction method on myocardial tomograms of normal subjects. Method: A total of 35 patients (20 female, 15 male) without evidence of cardiac disease underwent SPET with and without attenuation correction using a dual head camera and transmission data obtained by two scanning Gd-153 line sources after administration of 400 MBq Tc-99m-tetrofosmin. Results: In non-corrected (NC) stress studies the lowest count rates were found in the inferior segments with mean differences in count rates between maxima and minima of 35.8 ± 10.8%. In attenuation corrected (AC) images the respective segmental differences averaged only 20.9 ± 3.3% and the images did not show significant count deficiency in the inferior segments. The effects of correction revealed to be sex dependent, but independent of body mass on average. Conclusion: AC using the above technique significantly reduces the variability of count rate distribution in normal subjects and improves the preconditions for accurate diagnostic evaluation of coronary artery disease using SPET.
Keywords: Attenuation correction; myocardial scintigraphy; single photon emission tomography; Gd-153 transmission